Eating disorders: When social rank perceptions are shaped by early shame experiences. (24th March 2014) - Matos, Marcela; Ferreira, Cláudia; Duarte, Cristiana; Pinto‐Gouveia, José
<x xml:space="preserve">Abstract</x> Objectives Recent research has shown that early adverse experiences can be an important risk factor for eating disorders. However, the role of early shame memories and how they are structured as traumatic and central memories to self‐identity in eating disorders has never been investigated. This study explores the phenomenology of shame memories involving attachment figures and other agents from the wider social domain in patients with eating disorders, and examines the relationship between their traumatic and centrality features, social comparison based on physical appearance, and the severity of eating psychopathology. Design The study has a cross‐sectional design using a structured interview to assess retrospective data. Methods Participants in this study were 36 patients with an eating disorder diagnosis, who were assessed using Eating Disorder Examination (EDE 16.0D), the Shame Experiences Interview (SEI), and self‐report instruments measuring the traumatic features and centrality to identity of shame memories and social comparison. Results Results indicated that the traumatic and centrality qualities of shame memories involving social agents other than attachment figures (e.g., peers) are significantly correlated with unfavourable social rank perceptions and with increased eating psychopathology severity. Furthermore, the impact of such shame memories on eating psychopathology is fully mediated by social comparisons based on physical appearance. Conclusions These findings highlight the importance of early shame experiences involving peers and other social agents that become traumatic memories, central to self‐identity, to eating disorder patients' perceptions of inferiority and their core psychopathology features. Practitioner points Early shame experiences of patients with eating disorders should be carefully assessed. Shame traumatic memories involving social agents outside the family circle (e.g., peers) seem to be especially damaging for patients with eating disorders, and influence how physical appearance is used as a central dimension to establish their social rank. Practitioners should directly work with these shame memories, focusing on diminishing their traumatic nature and reconstruct their central meaning to self‐identity.